Desenvolvimento de massas alimentícias tipo talharim adicionadas de faseolamina (Phaseolus vulgaris L.) e farinha de linhaça (Linum usitatissimum L.) - Melo, Cícera Alyne Lemos (2018)
Currently there on interest of the part of consumers with healthy food, aiming to prevent chronic diseases caused by poor eating habits. The development of new enriched food products, with claimed action on prevention or reduction of certain diseases, has been increasing the health benefits of consumers, besides having a potential market growth. The pasta is considered an essential item at the table of Brazilian, it can be basically made with wheat flour, it is an energetic food, but with some nutritional deficiencies. Thus, it is of fundamental importance to develop research on raw materials that partially replace wheat flour, or to add ingredients that improve the nutritional and sensorial quality of the product. To develop this study, linseed flour (Linum usitatissimum L.) was selected because they are rich in several essential nutrients, and Phaseolamine (Phaseolus vulgaris L.), which has been used as a phytoterapic by obese and diabetics. In this context, the objective of this work was to develop and characterize pasta added with phaseolamine (Phaseolus vulgaris L.) and linseed flour (Linum usitatissimum L.), evaluating the physical, chemical, and nutritional parameters. To verify the in vivo glycemic index of the pasta and the physiological behaviors of healthy mice, subject to the daily supplementation of the pasta. It was applied the Central Rotational Compound Design (CRCD), where the independent variables were the content of phaseolamine, added in percentages ranging from 5 to 15%, and linseed flour added with percentages of 5 to 10%, calculated in relation to 100 g of wheat flour. For the formulation of the pasta there was no reduction of the wheat flour, 100 grams of the flour was added, and the other ingredients were calculated proportionally. The results of the physical parameters and cooking quality of the pasta in the development of the formulations through the CRCD were analyzed by surfaces of response and their respective contour curves through analysis of variance (ANOVA) and Tukey's test. After checking the influence of treatment levels, the formulations were chosen according to the following technological criteria: cooking time, weight gain, volume increase and solids loss. The selected samples were submitted to physical and chemical analyzes food fiber, color and scanning electron microscopy (SEM). The glycemic index was evaluated in vivo using Swiss mice (Mus musculus) females, healthy, according to appropriate methodology, obtaining the area of the standard food (white bread) and food tests, being the calculation of the areas performed by the trapezoidal rule. During the in vivo experiment, parameters of fasting blood glucose, body weight changes, food efficiency ratio (FER) and some physiological aspects, such as the amount of feed and water consumed, were also observed. The results obtained in the hydration characteristics of the mixed flours demonstrate that they had the capacity to absorb water and the swelling power reduced with water at 100 oC. In the parameters of pasta quality, there were no differences in weight and volume increase, but the solids content and cooking time were significantly reduced, characterizing them as good quality pasta. The composition of the noodles was also influenced by the addition of these ingredients: there was a reduction in carbohydrate content, significant increases in protein content (12.15% and 15.67%) and lipid content (8.9% and 9.3%). The amount of total dietary fiber, also, was significantly increased, in percentages that reached 41.70%, compared to the conventional type pasta. Analysis of images obtained by SEM verified that the enrichment did not bring damages to the surface and structure. The biological assays the values obtained for the Glycemic Index (GI) of the masses demonstrated the potential of these ingredients to reduce GI of food matrices, average GI of 36.58 and 23.17 were verified, classifying them as low glycemic index foods. During the monitoring of the physiological aspects of the mice, submitted to the daily administration of the noodles, the results demonstrated a significant reduction in fasting glycemia. Group 2 that received the formulation M1, containing 100 g of wheat flour, 10 g of phaseolamine and 3.96 g of linseed flour, obtained a mean reduction in basal glycemia of 23.96%. On the other hand, group 3, which was given the formulation M2, with 100 g of wheat flour, 15 g of phaseolamine and 5 g of linseed flour, reduced fasting glucose by 30.32%, both compared to the glycemia measured at baseline of the experiment, before starting the daily supplementation of the samples. Thus, pasta added with Faseolamine (Phaseolus vulgaris L.) and linseed flour (Linum usitatissimum L.) can be considered as an alternative to conventional pasta substitution, in view of nutritional enrichment, mainly of the worst fiber, and low glycemic index, and may help prevent the incidence of metabolic diseases.